On Cyclonic Tracks over the Eastern Mediterranean - H. A. Flocas; I. Simmonds; J. Kouroutzoglou; K. Keay; M. Hatzaki; V. Bricolas; D. Asimakopoulos (Journal of Climate, 2010)
In this study, an updated and extended climatology of cyclonic tracks affecting the eastern Mediterranean region is presented, in order to better understand the Mediterranean climate and its changes. This climatology includes intermonthly variations, classification of tracks according to their origin domain, dynamic and kinematic characteristics, and trend analysis. The dataset used is the 1962–2001, 2.58 3 2.58, 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA-40). The identification and tracking of the cyclones was performed with the aid of the Melbourne University algorithm. It was verified that considerable intermonthly variations of track density occur in the eastern Mediterranean, consistent with previous studies for the entire Mediterranean, while further interesting new features have been revealed. The classification of the tracks according to their origin domain reveals that the vast majority originate within the examined area itself, mainly in the Cyprus area and the southeastern Aegean Sea, while the tracks that originate elsewhere most frequently enter from the west. Deeper cyclones follow the southwest track originating from the area between Algeria and the Atlas Mountains. A greater size characterizes the westerly tracks (southwest, northwest, and west), while the northwest tracks propagate faster over the study area. A negative trend of the track frequency was found on an annual basis that can be mostly attributed to the winter months, being associated with variations in the baroclinicity. This negative trend is more prominent for the westerly and northeasterly tracks, as well as for those originating in the northern part of the examined area.